2019
DOI: 10.1016/j.jvs.2018.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of carotid plaque morphology (geometry and tissue composition) using computed tomography angiography

Abstract: Objective: Quantification of carotid plaque morphology (geometry and tissue composition) may help stratify risk for future stroke and assess plaque progression or regression in response to medical risk factor modification. We assessed the feasibility and reliability of morphologic measurements of carotid plaques using computed tomography angiography (CTA) and determined the minimum detectable change in plaque features by this approach. Methods: CTA images of both carotid arteries in 50 patients were analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 49 publications
(45 reference statements)
1
18
0
Order By: Relevance
“…13,14,27,28 The introduction of a new CT criterion ( 25 HU of attenuation) for the detection of IPH applied to the use of volumetric quantification analysis systems could allow one to extrapolate the real impact of the IPH component. Recently published articles in 2019 29,30 have demonstrated that the volumetric analysis of the carotid artery plaques obtained by CT data is a reliable technique and that small changes in plaque composition can also be detected. 30 In past years, the classic division of the carotid artery plaque type according to the attenuation values was based on the seminal study by de Weert et al, 24 in which 3 classes were identified: lipid (<60 HU), mixed (between 60 and 130 HU), and calcified (>130 HU).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14,27,28 The introduction of a new CT criterion ( 25 HU of attenuation) for the detection of IPH applied to the use of volumetric quantification analysis systems could allow one to extrapolate the real impact of the IPH component. Recently published articles in 2019 29,30 have demonstrated that the volumetric analysis of the carotid artery plaques obtained by CT data is a reliable technique and that small changes in plaque composition can also be detected. 30 In past years, the classic division of the carotid artery plaque type according to the attenuation values was based on the seminal study by de Weert et al, 24 in which 3 classes were identified: lipid (<60 HU), mixed (between 60 and 130 HU), and calcified (>130 HU).…”
Section: Discussionmentioning
confidence: 99%
“…Recently published articles in 2019 29,30 have demonstrated that the volumetric analysis of the carotid artery plaques obtained by CT data is a reliable technique and that small changes in plaque composition can also be detected. 30 In past years, the classic division of the carotid artery plaque type according to the attenuation values was based on the seminal study by de Weert et al, 24 in which 3 classes were identified: lipid (<60 HU), mixed (between 60 and 130 HU), and calcified (>130 HU). With the demonstration that attenuation values of <25 HU are due to IPH, 10 we tried to test the effect of the volumes for this component; therefore, the lipid class was divided into IPH (<25 HU) and lipid-IPH (from 26 to 59 HU).…”
Section: Discussionmentioning
confidence: 99%
“…Carotid plaques were assessed in pre-operative CT angiographies using a semi-automated, histology-validated software as previously described (The vascuCAP ® (Elucid Bioimaging Inc., Boston, MA, USA) software) [ 36 , 37 , 38 , 39 , 40 , 41 ]. In brief, reconstructed images were analyzed in a blinded fashion by one observer (EK) to characterize plaque structure and composition (plaque morphology) [ 4 ] creating 3D segmentations with improved resolution and soft tissue plaque component differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…In the study of carotid plaque, it is important to consider that the contribution of different features to the occurrence of cerebrovascular events varies greatly. Some morphological, biomechanical, and pathological features are thought to be related to plaque progression (Takaya et al, 2006;Chrencik et al, 2019;Wang et al, 2019). First of all, morphological and biomechanical features such as plaque area and plaque burden can be used to predict the progression of plaque and have been proved more accurate than a single risk factor (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…First of all, morphological and biomechanical features such as plaque area and plaque burden can be used to predict the progression of plaque and have been proved more accurate than a single risk factor (Wang et al, 2019). In addition, little change in plaque geometry and quantitative analysis of pathological tissue composition is useful to track plaque progression or regression and the assessment of the risk of plaque rupture (Sheahan et al, 2018;Chrencik et al, 2019;Lu et al, 2019). More recently, studies have suggested that plaque progression may also be related largely to hemodynamics (Eshtehardi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%